Identification, characterization, and purification of xylanase PC-01 isolated from Pacet hot spring - Ni Nyoman Purwani, Mamik Damayanti,; Dwi Purwadi, Ni Made; Fithri, Lailatul (Opción, 2019)
This research aims to characterize, identify and purify the xylanolytic enzymes by hydrophobic interaction and anion exchange chromatography via the endo-β-xylanase activity test with the DNS method. The best results obtained from anion-exchange chromatography of third fraction pH 5 with the purity level of 78.25 times higher than crude extract. In conclusion, Characteristics of bacterial isolates PC-01 are rod-shaped bacterial cells, Gram-positive, and have subterminal oval endospores.